Laporan Pertama tentang Infeksi Polerovirus pada Tanaman Cabai di Daerah Bali, Indonesia - Gede Suastika; Sedyo Hartono; I Dewa Nyoman Nyana; Tomohide Natsuaki (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
During a visit to Bali Island in September 2011, we found chilipepper plants exhibiting yellowing symptoms. The infected plants showed quite similar symptom to those of the recently reported Pepper yellow leaf curl virus from Israel and Japan, but there was no shortening of internodes or leaf rolling. We have ampliﬁed part of the genome of a virus associated with this disease using degenerate primers for members of the genus Polerovirus. The reverse transcription-polymerase chain reaction (RT-PCR) from symptom-bearing samples resulted in the amplification of a 650 bp band which is the expected size. RT-PCR from healthy samples did not produce an amplicon. Based on our results, we concluded that yellowing disease on chilipepper observed in Payangan, Gianyar, Bali is associated with a virus belonging to the genus Polerovirus. This is the first report on Polerovirus infection in chilipepper in Indonesia. Some researches for elucidation of the virus species and biological/molecular characters are being conducted.Key word: chilipepper, Indonesia, Polerovirus